2017
DOI: 10.17750/kmj2017-729
|View full text |Cite
|
Sign up to set email alerts
|

The peculiarities of focal epilepsy in pregnant women

Abstract: Aim. To investigate the peculiarities of focal epilepsy in pregnant women. Methods. 70 pregnant women with symptomatic focal epilepsy during the period from 2013 to 2017 were studied. Results. The average age at the onset of epilepsy was 18.2±0.6 years. The average duration of epilepsy by the time of pregnancy was 6.6±0.7 years. 15 (21.4±4.9%) women remained seizure-free during pregnancy. Seizures during pregnancy were observed in 55 (78.6±4.9%) women: seizure frequency increased in 22 (31.4±5.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In our study, the new-onset seizures during pregnancy occurred in 12 women (10.7%). The proportion of new-onset focal epilepsy was lower (4/116, 3.4%) in study of Yakunina et al [34]. Other studies by Tsivtsivadze et al [35] and Li et al [33] also showed the lowest rate of new-onset epilepsy during pregnancy (5/129, 4.0% and 22/1041, 2.1%, respectively).…”
Section: Discussionmentioning
confidence: 77%
“…In our study, the new-onset seizures during pregnancy occurred in 12 women (10.7%). The proportion of new-onset focal epilepsy was lower (4/116, 3.4%) in study of Yakunina et al [34]. Other studies by Tsivtsivadze et al [35] and Li et al [33] also showed the lowest rate of new-onset epilepsy during pregnancy (5/129, 4.0% and 22/1041, 2.1%, respectively).…”
Section: Discussionmentioning
confidence: 77%
“…In other stud ies, the pro por tion was higher. Melikova stud ied 70 preg nant women with fo cal ep i lepsy and 8 (11.4%) of them presented with a first-time ep i lep tic sei zure dur ing preg nancy [8]. In an other study from Azerbaijan, 112 preg nant women with ep i lepsy were eval u ated and 12 (10.7%) had their first sei zures dur ing preg nancy [3].…”
Section: Discussion and Lit Er A Ture Re Viewmentioning
confidence: 98%